KAJIAN PROGRES PERANAN KEPOLISIAN DALAM SISTEM PERADILAN PIDANAKAJIAN PROGRES PERANAN KEPOLISIAN DALAM SISTEM PERADILAN PIDANA - Fikry Latukau (TAHKIM, 2019)
In this paper, what the police want to discuss is the entry point for law enforcement in Indonesia. Police as the gatekeepers of the criminal justice system have a central role, because the criminal justice system starts from the Police. In Indonesia there are many violations that have all been regulated and processed according to the applicable law in Indonesia and which have been regulated in the Law of various violations but there are also violations that cannot be resolved with various and varied reasons. In this article also raised some hot issues that have not been resolved so that shows that the Police in this case included in the sub-system of criminal justice system is considered to be very, very decisive success and not based on law enforcement practices because his position is considered as the beginning of the law enforcement practice.